Chinese herbal medicine xuebijing injection for acute pancreatitis: An overview of systematic reviews - Zhu, Fengya; Yin, Shao; Zhou, Li; Li, Zimeng; Yan, Hui; Zhong, Yue; Wu, Xiaohan; Luo, Biao; Yang, Lanying; Gan, Daohui; Deng, Lvyu; Che, Deya; et al. (Frontiers in Pharmacology, 2022)
Background: At present, a number of systematic reviews (SRs) on Xuebijing injection (a patent in China) in the treatment of acute pancreatitis (AP) or severe acute pancreatitis (SAP) have been published. However, the quality of evidence is uneven and has not been comprehensively evaluated. Results: Nine eligible SRs were included, including 92 RCTs and 6,837 participants. Most of the SRs structure were relatively intact. However, the methodological quality of SRs were critically low. RoB rated 5 SRs as low risk of bias and 4 SRs as high risk of bias. In GRADE, a total of 47 results were included in the 9 SRs, of which 5 results (10.64%) were moderate quality, 22 results (46.81%) were low quality, and 20 results (42.55%) were very low quality. Meta-analysis results showed that Xuebijing injection combined treatment increased the total effectiveness rate of AP patients (RR = 1.19, 95% CI 1.17–1.23, P < 0.0001). Compared with the control group, Xuebijing injection group shortened the abdominal pain and distension relief time in AP patients (WMD = -1.69, 95% CI -1.88– -1.50, P < 0.0001; WMD = -1.48, 95% CI -1.74– -1.23, P < 0.0001), with high heterogeneity (I2 = 84.3%, P = 0.000; I2 = 72.2%, P = 0.000). Serum amylase level was also reduced (WMD = -2.06, 95% CI -2.47– -1.64, P < 0.0001), with significant heterogeneity (I2 = 71.6%, P = 0.000). Conclusion: Our evidence still supports the clinical value of Xuebijing injection as an analgesic and anti-inflammatory Chinese medicine preparation in the treatment of AP/SAP. One case of SR reported ADRs, and combined with the ADRs data in the real world, Xuebijing injection was well tolerated, and its safety could be guaranteed under the premise of strengthening quality control and standardized use. However, the high risk of bias in the original RCTs and the low methodological quality of SRs reduced the credibility of the efficacy and safety of Xuebijing injection for AP/SAP. Therefore, it is still the direction of researchers' efforts to follow CONSORT Statement for high-quality RCTs and PRISMA chicklist for SR reports.